Strengthening Legal Literacy and Preventive Strategies to Combat Sexual Violence at Kiai Haji Achmad Shiddiq State Islamic University of Jember - Martoyo Martoyo; St. Sariroh (Journal of Community Development, 2026)
Sexual violence in higher education institutions is a serious issue that requires comprehensive attention, particularly through the strengthening of legal literacy and sustained preventive efforts. This community service program aims to enhance the legal understanding and awareness of the academic community at the State Islamic University of Kiai Haji Achmad Shiddiq Jember regarding the prevention and handling of sexual violence on campus. The program employed a Participatory Action Research (PAR) approach, which emphasizes three interrelated elements: participation, research, and action. The activities were implemented through workshops, focus group discussions (FGDs), and simulations or role-playing exercises. The participants included students, lecturers, and administrative staff. The results indicate a significant increase in the level of legal awareness among the academic community, particularly in relation to regulations on sexual violence, which rose by 41.3%, understanding of the forms of sexual violence by 30%, and knowledge of reporting mechanisms by 21%. In addition, awareness of prevention programs, access to information, and the roles of relevant institutional bodies also showed consistent improvement. it could be effective not only in strengthening conceptual understanding but also in improving the structural and procedural aspects. Strengthening legal literacy and preventive measures represents a strategic step for higher education institutions in fostering a safe, inclusive, and dignified campus environment. Strong legal awareness contributes to the development of a just academic culture that respects human rights and promotes collective responsibility, thereby making the prevention of sexual violence an integral part of campus life.